Ionised hypocalcaemia in emergency and acute medicine. Issue 11 (14th November 2022) - Yates, Gregory P; Barrett, Alice; Ogedengbe, Onesi
Abstract : Acute hypocalcaemia can be life-threatening and must be diagnosed promptly. The gold-standard investigation is ionised calcium, which is measured on most blood gas analysers. Total calcium measurements are inaccurate in severe depletion even if 'corrected' or 'adjusted' for albumin. We present an illustrative case of a woman in her 30s with symptomatic hypocalcaemia and a very low ionised calcium on VBG analysis. Emergency calcium replacement was delayed due to a falsely reassuring corrected calcium result. Our discussion includes a systematic literature review on the use of ionised calcium in emergency and acute medical settings. We suggest cognitive biases that may explain clinical over-reliance on corrected calcium, and call for the inclusion of ionised calcium values in major treatment guidelines for acute hypocalcaemia.